Age of epilepsy onset as modulating factor for naming deficit after epilepsy surgery: a voxel-based lesion-symptom mapping study - Reindl, Caroline; Walther, Katrin; Allgäuer, Anna-Lena; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Schwarz, Michael; Trollmann, Regina; Madzar, Dominik; Knott, Michael; Dörfler, Arnd; et al. (Scientific Reports, 2023)
Age at onset of epilepsy is an important predictor of deterioration in naming ability following epilepsy surgery. In 141 patients with left hemispheric epilepsy and language dominance who received epilepsy surgery at the Epilepsy Centre Erlangen, naming of objects (Boston naming test, BNT) was assessed preoperatively and 6 months postoperatively. Surgical lesions were plotted on postoperative MRI and normalized for statistical analysis using voxel-based lesion-symptom mapping (VBLSM). The correlation between lesion and presence of postoperative naming deterioration was examined varying the considered age range of epilepsy onsets. The VBLSM analysis showed that volumes of cortex areas in the left temporal lobe, which were associated with postoperative decline of naming, increased with each year of later epilepsy onset. In patients with later onset, an increasing left posterior temporobasal area was significantly associated with a postoperative deficit when included in the resection. For late epilepsy onset, the temporomesial expansion also included the left hippocampus. The results underline that early onset of epilepsy is a good prognostic factor for unchanged postoperative naming ability following epilepsy surgery. For later age of epilepsy onset, the extent of the area at risk of postoperative naming deficit at 6 months after surgery included an increasing left temporobasal area which finally also comprised the hippocampus.
CRIS-Team Scopus Importer:2023-09-08

Anforderungen an die Neurorehabilitation nach epilepsiechirurgischen Eingriffen im linken Temporallappen bei Patienten mit neurokognitivem Risikoprofil - Schwarz, Michael; Badstübner, Annabell Sophie; Meyn, Karlotta; Walther, Katrin; Hamer, Hajo (Fortschritte der Neurologie - Psychiatrie, 2023)
Introduction In case of pharmacoresistant focal epilepsy, surgery is often the only way to achieve seizure freedom. These operations may result in cognitive deficits, especially with surgery in the left temporal lobe. The aim of this study was to determine whether patients operated in the left or right tem-poral lobe, respectively, have different cognitive outcomes. Furthermore, it was investigated if there was a positive influence of occupational therapy on neurorehabilitation in epilepsy patients. Methods In all patients cognitive performance was assessed preoperatively and six months postoperatively. Patient groups with surgery in the right and left temporal lobe were compared. Additionally, single cases of patients who had undergone extensive pre- and postoperative occupational therapy were analyzed. Results There was a significantly better cognitive outcome in patients who underwent surgery in their right temporal lobe. Occupational therapy was highly beneficial in patients after left temporal lobe surgery. Conclusion Occupational therapy after left temporal lobe surgery is adapted to find individual solutions for the patient s problems and to implement effective cognitive training strategies.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Epilepsie; Epilepsiechirurgie; Ergotherapie; Neuropsychologie; Temporallappen

A novel splice variant expands the LAMC3-associated cortical phenotype to frontal only polymicrogyria and adult-onset epilepsy - Kasper, Burkhard; Kraus, Cornelia; Schwarz, Michael; Rösch, Julie; Thiel, Christian; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2020)
Bi-allelic loss-of-function variants in LAMC3, encoding extracellular matrix protein laminin gamma 3, represent a rare cause of occipital polymicrogyria with epilepsy, developmental delay and cognitive impairment. So far, only five families have been reported. We now identified a novel, homozygous splice variant in LAMC3 in an individual with an unusual manifestation of cortical malformation. She presented with polymicrogyria in the frontal but not the occipital lobes, with adult-onset seizures and normal psychomotor development and cognition. Additionally, ictal asystole, requiring implantation of a pacemaker, and nonepileptic seizures occurred. This case expands the spectrum of LAMC3-associated cortical malformation phenotypes to frontal only polymicrogyria and adult-onset of epilepsy.
CRIS-Team Scopus Importer:2020-09-18
Keywords: cortical malformation; epilepsy; LAMC3; polymicrogyria; seizures

Deficits in cognitive estimation in patients with right-frontal and right-temporal lobe epilepsy Neuropsychologische Schätzdefizite bei rechtsfrontaler und rechtstemporaler Epilepsie - Schwarz, Michael; Benkowitsch, Edith; Schneider, Katrin; Walther, Katrin; Hamer, Hajo (Zeitschrift für Neuropsychologie, 2021)
Background: Previous studies revealed a right-hemispheric dominance for cognitive estimation processes. Objectives: This study explored estimation impairments in patients with focal temporal and frontal lobe epilepsies. Methods: 109 patients (right frontal, left frontal, right temporal-mesial, right temporal-neocortical, left temporal-mesial, left temporal-neocortical) and a control group with 67 subjects were included. All subjects underwent an extensive neuropsychological assessment including the Test zum kognitiven Schätzen (TKS; Brand et al., 2002). Hypothesis: It was expected that right-hemispheric lesions would be associated with impairments in cognitive estimation. Results: Patients with right-frontal and right-temporal mesial focus showed significant estimation deficits compared to the other groups. Conclusion: This study shows that the right hemisphere dominantly participates in cognitive estimation.
CRIS-Team Scopus Importer:2021-06-11
Keywords: cognitive estimation; epilepsy; frontal lobe; hippocampus; laterality; temporal lobe

Differential influence of hippocampal subfields to memory formation: insights from patients with temporal lobe epilepsy - Coras, Roland; Pauli, Elisabeth; Li, Jinmei; Schwarz, Michael; Roessler, Karl; Buchfelder, Michael; Hamer, Hajo; Stefan, Hermann; Blümcke, Ingmar (Brain, 2014)
To clarify the anatomical organization of human memory remains a major challenge in clinical neuroscience. Experimental data suggest dentate gyrus granule cells play a major role in memory acquisition, i.e. pattern separation and rapid pattern completion, whereas hippocampal CA1 neurons are implicated in place memory and autobiographical memory retrieval. Patients with temporal lobe epilepsy present with a broad spectrum of memory impairment, which can be assessed during clinical examination. Although long seizure histories may contribute to a pathophysiological reorganization of functional connectivity, surgical resection of the epileptic hippocampus offers a unique possibility to anatomically study the differential contribution of hippocampal subfields to compromised learning and memory in humans. Herein, we tested the hypothesis of hippocampal subfield specialization in a series of 100 consecutive patients with temporal lobe epilepsy submitted to epilepsy surgery. Memory profiles were obtained from intracarotid amobarbital testing and non-invasive verbal memory assessment before surgery, and correlated with histopathologically quantified cell loss pattern in hippocampal subfields obtained from the same patients using the new international consensus classification for hippocampal sclerosis proposed by the International League against Epilepsy (HS ILAE). Interestingly, patients with CA1 predominant cell loss (HS ILAE Type 2; n = 13) did not show declarative memory impairment and were indistinguishable from patients without any hippocampal cell loss (n = 19). In contrast, 63 patients with neuronal loss affecting all hippocampal subfields including CA1, CA4 and dentate gyrus (HS ILAE Type 1), or predominant cell loss in CA4 and partially affecting also CA3 and dentate gyrus (HS ILAE Type 3, n = 5) showed significantly reduced declarative memory capacities (intracarotid amobarbital testing: P < 0.001; verbal memory: P < 0.05). Our results suggested an alternative model of how memory processing can be organized amongst hippocampal subfields, and that CA1 pyramidal cells are less critically involved in declarative human memory acquisition compared to dentate gyrus granule cells or CA4/CA3 pyramidal cells.
EVALuna2:7242

Explicit and implicit timing in mesial temporal lobe epilepsy patients - Hellweg, Annika; Schwarz, Michael; Walther, Katrin; Hamer, Hajo; Visalli, Antonino; Mioni, Giovanna (Epilepsy and Behavior, 2025)
Objectives: The present study investigates the explicit and implicit timing abilities of patients with mesial temporal lobe epilepsy (MTLE). Based on previous studies, it was hypothesized that timing abilities were decreased in MTLE patients. Methods: The performance of 21 MTLE patients and 21 neurologically healthy probands was tested on two separate tasks. The time bisection task was used to investigate explicit timing and the foreperiod task to test implicit timing. Results: For the time bisection task, less precise temporal judgements were found in the patient group compared to the control group. This was indicated by a flatter psychophysical curve in the patients compared to controls. Moreover, participants did not differ in term of precision, but patients were more variable than controls. There was no statistical difference between the performance of the control and the patient group in the implicit timing task. Both groups demonstrated the foreperiod effect, meaning that the RTs of the participants became shorter with longer durations. Conclusions: MTLE patients showed less precise temporal judgments in explicit timing, while their implicit timing was largely preserved. This finding suggests that explicit time perception should be routinely investigated in MTLE patients.
CRIS-Team Scopus Importer:2025-04-25
Keywords: Epilepsy; Explicit timing; Foreperiod task; Implicit timing; Time bisection task

Functional dissociation between cognitive estimation and object naming in focal temporal and frontal lobe epilepsies - Braun, Isabella; Schwarz, Michael; Walther, Katrin; Stemmler, Mark; Kasper, Burkhard; Hamer, Hajo (International Journal of Epilepsy, 2018)

Glucocorticoid modulation of synaptic plasticity in the human temporal cortex of epilepsy patients: Does chronic stress contribute to memory impairment? - Brandner, Sebastian; Schröter, Sarah; Çalışkan, Gürsel; Salar, Seda; Kobow, Katja; Coras, Roland; Blümcke, Ingmar; Hamer, Hajo; Schwarz, Michael; Buchfelder, Michael; Maslarova, Anna (Epilepsia, 2021)
Objective: Memory impairment is common in patients with temporal lobe epilepsy and seriously affects life quality. Chronic stress is a recognized cofactor in epilepsy and can also impair memory function. Furthermore, increased cortisol levels have been reported in epilepsy patients. Animal models have suggested that aggravating effects of stress on memory and synaptic plasticity were mediated via glucocorticoids. The aim of this study was, therefore, to investigate the effect of glucocorticoid receptor (GR) modulation on synaptic plasticity in the human cortex of epilepsy patients. Methods: We performed field potential recordings in acute slices from the temporal neocortex of patients who underwent surgery for drug-resistant temporal lobe epilepsy. Synaptic plasticity was investigated by a theta-burst stimulation (TBS) protocol for induction of long-term potentiation (LTP) in the presence of GR modulators. Results: LTP was impaired in temporal cortex from epilepsy patients. Pretreatment of the slices with the GR antagonist mifepristone (RU486) improved LTP induction, suggesting that LTP impairment was due to baseline GR activation in the human cortex. The highly potent GR agonist dexamethasone additionally weakened synaptic strength in an activity-dependent manner when applied after TBS. Significance: Our results show a direct negative glucocorticoid effect on synaptic potentiation in the human cortex and imply chronic activation of GRs. Chronic stress may therefore contribute to memory impairment in patients with temporal lobe epilepsy. Furthermore, the activity-dependent acute inhibitory effect of dexamethasone suggests a mechanism of synaptic downscaling by which postictally increased cortisol levels may prevent pathologic plasticity upon seizures.
CRIS-Team Scopus Importer:2021-10-29
Keywords: dexamethasone; epilepsy; human cortex; long-term potentiation; stress

Long-term outcome after epilepsy surgery in older adults - Lang, Johannes D.; Grell, Laura; Hagge, Mareike; Onugoren, Muejgan Dogan; Gollwitzer, Stephanie; Graf, Wolfgang; Schwarz, Michael; Coras, Roland; Blümcke, Ingmar; Sommer, Bjoern; Roessler, Karl; Buchfelder, Michael; et al. (Seizure-European Journal of Epilepsy, 2018)
PURPOSE: The incidence of epilepsy in older adults is growing, as does the incidence of comorbidities. Therefore, when it comes to epilepsy surgery in medically intractable epilepsy, age is often seen as a limiting factor. To investigate the outcome after epilepsy surgery in a population of older adults, we compared the benefit for patients aged 50-59 years with those aged 60 years and older in respect of efficacy and safety. METHOD: Patients aged ≥50 years with medically intractable epilepsy who underwent epilepsy surgery from 1990 to 2013 were selected from the database of a German epilepsy center. All of them received a standardised and detailed presurgical diagnostic evaluation. Follow-up included at least four scheduled visits with EEG, MRI and neuropsychological testing. Outcome was assessed using the Engel outcome scale. RESULTS: 79 patients aged between 50 and 67 years were followed-up for a median of 4.7 years (2-16 years). 68% of patients were free of disabling seizures (Engel class I, ≥60 years: 75%) and 58% were seizure-free (Engel class IA, ≥60 years: 70%). 90% of our patients suffered from temporal lobe epilepsy (TLE), 9% from frontal lobe epilepsy (FLE) and one occipital lobe epilepsy (OLE). After surgery, 9% discontinued or tapered their medication. Permanent surgical complications occurred in 10% of cases and transient neurological deficits were seen in 11%. Older patients had a higher risk for postoperative hygroma (≥60 years 15%; <60 years 8%) and were more prone to postoperative memory deficits (≥60 years 45%), especially after resection of the dominant temporal lobe. Verbal and figural memory testing did not differ significantly between the groups. CONCLUSIONS: The results support the view that in selected older patients, epilepsy surgery shows equal or even higher success rates as compared to younger patients. However, patients of older age may be at greater risk for postoperative hygroma and memory deficits, especially after dominant temporal lobe resections.
EVALuna2:34593

Psychogenic nonepileptic seizures: clinical characteristics and outcome - Volbers, Bastian; Walther, Katrin; Kurzbuch, Katrin; Erdmann, Laura; Gollwitzer, Stephanie; Lang, Johannes; Onugoren, Muejgan Dogan; Schwarz, Michael; Schwab, Stefan; Hamer, Hajo (Brain and Behavior, 2022)
Background: Clinical characteristics, outpatient situation, and outcome in patients with psychogenic nonepileptic seizures (PNES) remain to be elucidated. Methods: Patients diagnosed with PNES after video-electroencephalography (EEG) monitoring (VEM) 03/2000–01/2016 at the Erlangen Epilepsy Center were surveyed between June 2016 and February 2017. Primary outcome was PNES cessation defined as no PNES episodes within > = 12 months prior to the interview. Secondary outcome variables included quality of life (QoL) and dependency. Sensitivity analysis included patients with proven PNES during VEM without comorbid epilepsy. Results: Ninety-nine patients were included (median age 38 (interquartile range (IQR 29–52)) years; 68 (69%) females, follow-up 4 (IQR 2.1–7.7) years). Twenty-eight (28%) patients suffered from comorbid epilepsy. Twenty-five (25%) patients reported PNES cessation. Older age at symptom onset (odds ratio (OR) related to PNES cessation: 0.95 (95% CI 0.90–0.99)), comorbid epilepsy (OR 0.16 (95% CI 0.03–0.83)), anxiety disorder (OR 0.15 (95% CI 0.04–0.61)), and tongue biting (OR 0.22 (95% CI 0.03–0.91)) remained independently associated with ongoing PNES activity after adjustment. Sensitivity analysis (n = 63) revealed depressive disorder (OR 0.03 (95% CI 0.003–0.34)) instead of anxiety as independent predictor, while this seemed relevant only in patients older than 26 years at onset (OR 0.04 (95% CI 0.002–0.78) versus OR 0.21 (95% CI 0.02–1.84) in patients younger than 26 years). PNES cessation was associated with increased median QoL (8 (IQR 7–9) versus 5.5 (IQR 4–7); p <.001) and an increased frequency of financial independency (14 (56%) versus 21 (28%); p =.01). Conclusions: We found poor outcomes in PNES especially in older patients at onset with comorbid depressive disorder. Comorbid epilepsy also seems to be a major risk factor of ongoing PNES activity, which in turn affects patients’ daily living.
CRIS-Team Scopus Importer:2022-04-22
Keywords: activities of daily living; mental disorders; nonepileptic seizures; patient-relevant outcome; prognosis

Psychological long-term outcome in patients with psychogenic nonepileptic seizures - Walther, Katrin; Volbers, Bastian; Erdmann, Laura; Onugoren, Muejgan Dogan; Gollwitzer, Stephanie; Kasper, Burkhard; Kurzbuch, Katrin; Lang, Johannes; Schwab, Stefan; Schwarz, Michael; Hamer, Hajo (Epilepsia, 2019)
Objective To examine the long-term outcome of psychological status, personality, and health-related quality of life (HRQoL) in patients with psychogenic nonepileptic seizures (PNES) and to define predictors of favorable outcome of cessation of PNES. Method Patients diagnosed with PNES during video-electroencephalography (EEG) monitoring at the Erlangen Epilepsy Center were contacted 1-16 years after communicating the diagnosis. Follow-up information from each participant was obtained by interview (PNES outcome) and by self-reported questionnaires of psychological symptoms (Beck Depression Inventory-II, Symptom Checklist-90-Standard, Dissociative Symptoms questionnaire), personality traits (Freiburg Personality Inventory-Revised), and HRQoL (36-Item Short Form Health Survey). Results Fifty-two patients participated in the study (mean age +/- standard deviation [SD] 40.5 +/- 14.0 years; 75% female, follow-up: 5.3 +/- 4.2 years). Nineteen patients (37%) were free of PNES for the past 12 months. Patients with persisting PNES were older at disease onset (32.9 vs 22.3 years, P < 0.01) and diagnosis (40.5 vs 27.2 years, P < 0.001), and showed worse psychological functioning, lower extraversion and life satisfaction, and higher inhibitedness and worse HRQoL than PNES-free patients. Patients with cessation of PNES were within the normal range in all dimensions. Cessation of PNES was best predicted by younger age at PNES onset and higher extraversion. Significance Outcome of PNES is poor, psychopathology is high, and HRQoL is low in patients with persistent PNES but may normalize with PNES cessation. High introversion and older age at PNES onset are risk factors for persistent PNES.
CRIS-Team WoS Importer:2019-04-16

Psychosocial long-term outcome in patients with psychogenic non-epileptic seizures - Walther, Katrin; Volbers, Bastian; Erdmann, Laura; Kurzbuch, Katrin; Lang, Johannes; Müller, Tamara; Reindl, Caroline; Schwarz, Michael; Schwab, Stefan; Hamer, Hajo (Seizure-European Journal of Epilepsy, 2020)
Purpose: To evaluate psychosocial long-term outcome in patients diagnosed with psychogenic nonepileptic seizures (PNES) and to predict outcome of PNES, economic status, and quality of life (QoL) at follow-up. Methods: Patients diagnosed with PNES in the video-EEG-monitoring unit at our Epilepsy center between 2002–2016 were contacted by phone 1–16 years after communicating the diagnosis. Patients underwent a structured interview asking for current PNES status, psychosocial situation (economic status, marital status, setting of living, driving), depression, and QoL. Results: Of 70 PNES patients without comorbid epilepsy (age: 41.1 ± 13.5 years; 74 % female, follow-up: 5.2 ± 4.2 years), 23 patients (33 %) reported to be free of PNES during the last 12 months. Patients with cessation of PNES were younger at PNES onset (p < .01) and diagnosis (p < .01) and had a higher education (p < .05). At follow-up, the proportion of economically active patients only increased in individuals with cessation of PNES (p < .001) while an increased number of patients with persisting PNES relied on governmental support (p < .001). Cessation of PNES was associated with better mood (p < .01) and QoL (p < .001). In multiple regression models, cessation of PNES was only predicted by younger age at onset, while good economic outcome was determined by younger age and good economic status at diagnosis and cessation of PNES at follow-up. Good QoL at follow-up was predicted by low depressive symptoms, freedom of PNES, and economic activity at follow-up. Conclusion: Long-term outcome in patients with PNES remains to be poor and the majority of patients continue to have PNES. Cessation of PNES was associated with good economic outcome, mood, and QoL.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Employment; Long-term outcome; Marital status; Mood; Psychogenic non-epileptic seizures; Quality of life

Psychosocial outcome in epilepsy after extratemporal surgery - Walther, Katrin; Onugoren, Muejgan Dogan; Buchfelder, Michael; Gollwitzer, Stephanie; Graf, Wolfgang; Kasper, Burkhard; Kriwy, Peter; Kurzbuch, Katrin; Lang, Johannes; Roessler, Karl; Schwab, Stefan; Schwarz, Michael; et al. (Epilepsy and Behavior, 2018)
OBJECTIVE: Only limited data exist on psychosocial long-term outcome after epilepsy surgery in patients with extratemporal epilepsy. The aim of this study was to investigate psychosocial outcome after extratemporal epilepsy surgery and to assess factors predicting favorable outcome. METHOD: Sixty-five out of 104 eligible patients who had undergone extratemporal epilepsy surgery at our epilepsy center between 1990 and 2015 (mean age: 42.2. years; 75% of the resections in the frontal lobe) completed a questionnaire asking about seizure status, employment status, marital and living situation, driving status, depressive symptoms, and quality of life (QOL). Follow-up was on average 9.2years after surgery (range: 1-26years). RESULTS: Thirty-eight (58%) patients were free of disabling seizures (Engel class I), and 28 (43%) have not experienced any seizures after surgery (Engel class IA). Employment rate in the primary labor market remained at 45%, but more patients lost employment (14%) than gained employment (8%). Postoperative employment was predicted by preoperative employment (p=.007), seizure freedom (p=.025), older age at seizure onset (p=.018), younger age at follow-up (p=.035), and female gender (p=.048). Seizure-free patients were more likely to be driving; have a partner, particularly in males; and have lower depressive scores. Quality of life at follow-up was best predicted by employment (p=.012), partnership (p=.025), and seizure freedom (p=.025). In contrast, recurrence of seizures and early seizure onset were associated with poor psychosocial outcome, particularly in men. CONCLUSION: The study provides support that extratemporal surgery can lead to improved QOL and favorable psychosocial outcome. Seizure freedom is important but not the only determinant of good psychosocial outcome.
EVALuna2:35520

Resection of dominant fusiform gyrus is associated with decline of naming function when temporal lobe epilepsy manifests after the age of five: A voxel-based lesion-symptom mapping study - Reindl, Caroline; Allgäuer, Andrea; Kleiser, Benedict; Onugoren, Müjgan Dogan; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Winder, Klemens; Schwarz, Michael; Gollwitzer, Stephanie; Trollmann, Regina; Rösch, Julie; et al. (NeuroImage: Clinical, 2022)
Objective: To determine patients’ characteristics and regions in the temporal lobe where resections lead to a decline in picture naming. Methods: 311 patients with left hemispheric dominance for language were included who underwent epilepsy surgery at the Epilepsy Center of Erlangen and whose picture naming scores (Boston Naming Test, BNT) were available preoperatively and 6-months postoperatively. Surgical lesions were mapped to an averaged template based on preoperative and postoperative MRI using voxel-based lesion-symptom mapping (VBLSM). Postoperative brain shifts were corrected. The relationship between lesioned brain areas and the presence of a postoperative naming decline was examined voxel-wise while controlling for effects of overall lesion size at first in the total cohort and then restricted to temporal lobe resections. Results: In VBLSM in the total sample, a decline in BNT score was significantly related to left temporal surgery. When only considering patients with left temporal lobe resections (n = 121), 40 (33.1%) significantly worsened in BNT postoperatively. VBLSM including all patients with left temporal resections generated no significant results within the temporal lobe. However, naming decline of patients with epilepsy onset after 5 years of age was significantly associated with resections in the left inferior temporal (extent of BNT decline range: 10.8− 14.4%) and fusiform gyrus (decline range: 12.1−18.4%). Significance: Resections in the posterior part of the dominant fusiform and inferior temporal gyrus was associated with a risk of deterioration in naming performance at six months after surgery in patients with epilepsy onset after 5 years of age but not with earlier epilepsy onset.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Basal temporal language area; Epilepsy surgery; Gyrus fusiformis; Lesion localization; Naming; Neuropsychological outcome

Role of occupational therapy in epilepsy patients after left temporal lobe surgery - Schwarz, Michael; Geismar, Lisa; Schneider, Katrin; Kasper, Burkhard; Walther, Katrin; Hamer, Hajo (British Journal of Occupational Therapy, 2022)
There is a relevant risk of psychosocial as well as cognitive impairments in epilepsy patients with resective surgery in the left temporal lobe. Surgery in the speech-dominant hemisphere can be associated with deterioration of speech related functions including verbal memory. There are only limited studies addressing the impact of occupational therapy in postoperative rehabilitation of epilepsy patients.Method: In this study, a mixed-methods design based on the grounded theory concept was administered. Seven patients with left temporal lobe epilepsy and a risk profile for postoperative cognitive decline were investigated over various time points. Neuropsychological assessments occurred before surgery, 1 week, 3 months, and 6 months postoperatively. According to our rehabilitation concept, every patient started occupational therapy 1 month before surgery. Therapy lasted for at least 6 months after surgery. For all patients, extensive qualitative interviews with the occupational therapists and anamnestic data were analyzed.Results: In all patients, postoperative psychosocial difficulties emerged. Language and memory tests showed a decline after 6 months specifically for name retrieval. Occupational therapy was adapted to find individual solutions for the patients problems and to implement effective coping strategies.Conclusion: Cognitive training lead to consistent improvements over time. The results show that occupational therapy can be an efficient tool in the treatment of psychosocial and cognitive impairments after epilepsy surgery.
CRIS-Team WoS Importer:2022-03-04

WADA test for postoperative memory prediction in left TLE. Is it still useful in the 21st century? - Bruzsa, Ann Kathrin; Walther, Katrin; Kasper, Burkhard; Gollwitzer, Stefanie; Hamer, Hajo; Schwarz, Michael (Clinical Neurology and Neurosurgery, 2023)
Background: Epilepsy surgery offers an effective treatment to achieve seizure freedom in refractory temporal lobe epilepsy. Since left temporal lobe surgery can be associated with verbal memory deterioration, control of cognitive decline is a main goal of therapy. This study analyzes the prognostic value of intracarotid amobarbital procedure (Wada test) in addition to specific neuropsychological and clinical variables for postoperative memory changes. Method: Between 2013 and 2021 thirty-six patients (18 females, 18 males, mean age 41.0 years) from the Epilepsy Center Erlangen (ECE) with left hemispheric temporal lobe epilepsy underwent neuropsychological assessment preoperatively – including the Wada test – and six months postoperatively. In addition, a group of 92 patients (40 females, 52 males, mean age 36.1 years) with left or right hemispheric focus who underwent Wada test and surgery before 2013 was included as a standardization group. In all patients Wada test was carried out preoperatively to determine language dominance and memory capacity. Results: Postoperative verbal memory scores showed no significant difference from preoperative performance. Preoperative verbal memory performance as well as the hippocampal resection extent is particularly important in predicting postoperative verbal memory change. After left temporal lobe surgery, a significantly higher postoperative functional level was shown for figural memory. Specifically, a good contralateral hemispheric performance level assessed by the Wada test proved to be a compensatory factor for postoperative losses. Conclusion: The Wada test is no longer necessary as a diagnostic tool for a broad group of patients with temporal lobe epilepsy. However, it can be useful for a subgroup of patients with clinical indicators such as nonspecific or incongruent preoperative verbal and figural memory impairments. In this study, Wada test data about the functional level of the contralateral hemisphere specifically allowed estimation of postoperative figural memory changes.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Epilepsy surgery; Memory changes; Temporal lobe epilepsy; Wada test